Foundations of antenna engineering a unified approach for line-of-sight and multipath - Kildal, Per-Simon 1951- (Artech House antennas and electromagnetics analysis library, 2015)
"This is the first textbook that contains a holistic treatment of traditional antennas mounted on masts (Line-of-Sight antenna systems) and small antennas used on modern wireless devices that are subject to signal variations (fading) due to multipath propagation. The focus is on characterization and describing classical antennas by modern complex vector theory, thereby linking together many disciplines, such as electromagnetic theory, classical antenna theory, wave propagation, and antenna system performance."--Back cover